URGENSI NOTARIS SYARI’AH DALAM BISNIS SYARI’AH DI INDONESIA - Laurensius Arliman S. (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
The business development of the economy not only in the field of conventional, Shari'ah economic business now has started mushrooming everywhere. With a population of Indonesia is predominantly Muslim, the more it will attract market share to take part in business economics Shari'ah. Instead of that, the presence of a notary Shari'ah is urgently needed in Indonesia, because the focus of work in the field of economics Shari'ah, so it can ensure law and society in transacting Shari'ah. The research used normative juridical approach, using the theory of legal certainty. So we get Analisia, that the reality is that the people do not feel comfortable in transacting Shari'ah, because of the absence of provisions on rules of shari'a law notary. So the conclusion is obtained, the need for Shari'ah notary very important.